1994
DOI: 10.1021/bi00253a010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuronal Nitric Oxide Synthase and a C415H Mutant, Purified from a Baculovirus Overexpression System

Abstract: Nitric oxide synthase (NOS) catalyzes the conversion of L-arginine to citrulline and nitric oxide (.NO). A baculovirus overexpression system has been developed for a constitutive NOS isoform, cloned originally from rat cerebellum (B-NOS). Recombinant virus was used at a multiplicity of infection of 5 to infect Spodoptera frugiperda cells in culture, and NOS was expressed to 10% of the total soluble protein at 48 h postinfection. In order to express catalytically active enzyme, it was necessary to supplement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 44 publications
8
85
0
Order By: Relevance
“…After incubation at 37°C for 3 min, the conversion of arginine to citrulline was determined by ion exchange purification as described previously (18). The K m determined for arginine by this method was 4.4 M, which is consistent with that found by other laboratories (21,22).…”
Section: Methodssupporting
confidence: 92%
“…After incubation at 37°C for 3 min, the conversion of arginine to citrulline was determined by ion exchange purification as described previously (18). The K m determined for arginine by this method was 4.4 M, which is consistent with that found by other laboratories (21,22).…”
Section: Methodssupporting
confidence: 92%
“…This region contains the presumptive heme-and calmodulinbinding sites in mammalian NOS enzymes. The heme-binding site was proposed to be centered around C-415 in the nNOS (35,36), and this cysteine residue has been shown to be important for heme binding (37). The sequence surrounding the corresponding cysteine (C-329) in DNOS is well conserved.…”
Section: Resultsmentioning
confidence: 99%
“…Defining the amino acid residues making up the heme binding region and substrate oxidation site is a key step in unraveling the biochemistry of NO synthesis. The proximal heme thiolate ligand was first predicted by McMillan et al (12) and subsequently confirmed by site-directed mutagenesis and spectral analysis for three NOS isoforms (13)(14)(15)(16). However, due to the lack of a three-dimensional NOS structure and the lack of sequence homology of the NOS oxygenase domain to other P450s, it has been difficult to identify residues in the distal heme pocket responsible for L-arginine binding.…”
mentioning
confidence: 99%